2006
DOI: 10.1007/s11120-006-9054-z
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis research in Italy: a review

Abstract: This historical review was compiled and edited by Giorgio Forti, whereas the other authors of the different sections are listed alphabetically after his name, below the title of the paper; they are also listed in the individual sections. This review deals with the research on photosynthesis performed in several Italian laboratories during the last 50 years; it includes research done, in collaboration, at several international laboratories, particularly USA, UK, Switzerland, Hungary, Germany, France, Finland, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 252 publications
(190 reference statements)
0
4
0
Order By: Relevance
“…Actually a collaboration with Mario Orsenigo and his group never took off; however, it was on that occasion that GMG first met Roberto Bassi who had just been given a research position in the Institute of Botany headed by Mario. Soon a collaboration started since Bassi was interested in the description of the photosynthetic apparatus at molecular level and already had some experience, mainly in electron microscopy (see Forti et al 2006 for Bassi's contributions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually a collaboration with Mario Orsenigo and his group never took off; however, it was on that occasion that GMG first met Roberto Bassi who had just been given a research position in the Institute of Botany headed by Mario. Soon a collaboration started since Bassi was interested in the description of the photosynthetic apparatus at molecular level and already had some experience, mainly in electron microscopy (see Forti et al 2006 for Bassi's contributions).…”
Section: Introductionmentioning
confidence: 99%
“…However, also with the help of a younger scientist, Roberto Barbato, who had just obtained his degree in Biology, a laboratory was set up in the new Biology Building which was still to be completed and was expected to bring all the biologists together in a single place (Fig. 5), (see Forti et al 2006, for Barbato's contributions). The ability of the two Robertos (Bassi and Barbato) in separating the chlorophyll-protein complexes by non denaturing polyacrylamide gel electrophoresis was growing rapidly and, in short time, the 'green gels' from Padova were recognized by the photosynthetic community among the best obtainable.…”
Section: Introductionmentioning
confidence: 99%
“…DCMU blocks electron flow; nevertheless, cyclic electron flow still occurs (Joliot et al , 2006) and the plastoquinone pool may be reduced through chlororespiration (Bennoun, 1982). Thus, state transitions and NPQ may continue to occur (Forti et al , 2006). Although nigericin decreases the proton gradient, consequently decreasing NPQ, both the state transitions and NPQ may continue to some extent.…”
mentioning
confidence: 99%
“…It has been shown that cyclic electron flow exists in vivo (Joliot et al , 2006) and produces ATP (Majeran et al , 2001). The decreasing intensities and lifetimes in the presence of DCMU at ‘Hi’ light intensity could be due to either NPQ (Gilmore et al , 1998) or ‘state transitions’ (Forti et al , 2006), or both.…”
mentioning
confidence: 99%